Practical guidelines for antibiotic prescribing in breast surgery: antibiotic prophylaxis and treatment of surgical site infections and implant-associated infections - Kozlov R.S.; Kaprin A.D.; Andreeva I.V.; Zikiryakhodzhaev A.D.; Vlasova M.Y.; Dekhnich A.V.; Dovgan E.V.; Kovalenko T.N.; Mikhaylov S.I.; Stetsiouk O.U. (Клиническая микробиология и антимикробная химиотерапия)
Breast surgery is a broad field that includes both surgical treatment of breast diseases and various variants of reconstructive and plastic surgeries for breast correction. Despite the fact that according to the accepted classification breast interventions are considered to be «clean», the incidence of infectious complications in surgical treatment of breast cancer is higher than in conventional «clean» surgical interventions, and the rate increases significantly in case of one-stage breast reconstruction with expanders or implants. In these practical guidelines for the first time in Russia a detailed analysis of the available current publications on antibiotic prophylaxis and treatment of infectious complications (surgical site infections and implantassociated infections) is presented and specific schemes of antibiotic use in breast surgery for both breast cancer and reconstructive-plastic surgeries are proposed.